Preclinical Evaluation of the Thrombogenicity and Endothelialization of Bare Metal and Surface-Coated Neurovascular Stents - Krajewski, S.; Neumann, B.; Kurz, J.; Perle, N.; Avci-Adali, M.; Cattaneo, G.; Wendel, H.P. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Stent-assisted coiling is routinely used for the endovascular treatment of complex or wide-neck intracranial aneurysms. However, in-stent thrombosis, thromboembolic events, and ischemic complications remain a major concern associated with stent implants. Therefore, a novel low-profile neurovascular stent with a bare metal surface was investigated with regard to thrombogenicity and endothelialization and compared with the same stent coated with albumin or heparin. MATERIALS AND METHODS: The bare metal and heparin- or albumin-coated stents were loaded in heparin-coated tubing, which was then filled with heparinized human blood (n = 5) and circulated at 150 mL/min and 37°C for 60 minutes. Before and after circulation, measurement of various inflammation and coagulation markers and scanning electron microscopy were performed. Endothelialization of the stents was investigated in an in vitro model including human umbilical vascular endothelial cells. RESULTS: Our results showed that platelet loss and platelet activation and activation of the coagulation cascade, which are induced by the bare metal stents, were significantly reduced by heparin or albumin coating. Adverse effects on erythrocytes, leukocytes, and the complement cascade were not induced by the bare metal or coated stents. Moreover, the bare metal and albumin-coated stents showed good endothelialization properties. CONCLUSIONS: Albumin and heparin coatings clearly improve the thrombogenicity of the stents and thus may represent fundamental progress in the treatment of intracranial aneurysms. Moreover, preclinical evaluation of neurovascular stents under physiologic conditions supports and accelerates the development of more biocompatible neurovascular stents. HUVECshuman umbilical vascular endothelial cellsSEMscanning electron microscopyTATthrombin-antithrombin III